Analysis of the Effect of Transformational Leadership, Communication, and Job Stress on Employee Work Ethic at PT Bank Danamon Indonesia Tbk (A Study at the Head Office of Danamon Simpan Pinjam) - Puspitasari, Anita Dwi (Priviet Social Sciences Journal, 2023)
This study aims to analyze the influence of transformational leadership, communication, and job stress on employee work ethic at the Head Office of Danamon Simpan Pinjam. The research employs a quantitative approach using survey data collected through questionnaires distributed to 80 employees. Data analysis is conducted using descriptive statistics and multiple linear regression with the assistance of SPSS. The results of the study indicate that transformational leadership and communication have positive and significant effects on employee work ethic, while job stress has a negative and significant effect. Transformational leadership contributes to shaping positive employee attitudes through trust, respect, and motivation, while effective communication enhances collaboration and organizational interaction. On the other hand, job stress negatively impacts employee performance, particularly when related to limited career development opportunities. Simultaneously, transformational leadership, communication, and job stress significantly influence employee work ethic, with a combined contribution of 57.8%. This finding suggests that organizational factors play a crucial role in determining employee work ethic, although other variables outside the scope of this study also contribute. Overall, the study highlights the importance of strengthening leadership quality and communication practices while minimizing job stress to improve employee work ethic and organizational effectiveness.